FDI and migration of skilled workers toward developing countries: firm-level evidence from Sub-Saharan Africa - (:unkn) unknown (My University, 2015)
This paper investigates the determinants of the employment of foreign skilled workers by firms operating in Sub-Saharan African countries. We use cross section firm-level data on a large sample of foreign and domestic firms collected through the UNIDO Africa Investor Survey 2010. We find evidence of a strong complementarity between foreign capital inflows and the employment of foreign skilled workers.Our results also indicate that interventions in improving the working regulation and skilled workers immigration regimes may stimulate foreign skilled workers transfer by firms, and thereby foreign direct investments.
Keywords: African Research